Interspecies transmission of simian foamy virus in a natural predator-prey system - Leendertz, Fabian H; Zirkel, Florian; Couacy-Hymann, Emmanuel; Ellerbrok, Heinz; Morozov, Vladimir A; Pauli, Georg; Hedemann, Claudia; Formenty, Pierre; Jensen, Siv Aina; Boesch, Christophe; Junglen, Sandra (Journal of virology, 2008)
Simian foamy viruses (SFV) are ancient retroviruses of primates and have coevolved with their host species for as many as 30 million years. Although humans are not naturally infected with foamy virus, infection is occasionally acquired through interspecies transmission from nonhuman primates. We show that interspecies transmissions occur in a natural hunter-prey system, i.e., between wild chimpanzees and colobus monkeys, both of which harbor their own species-specific strains of SFV. Chimpanzees infected with chimpanzee SFV strains were shown to be coinfected with SFV from colobus monkeys, indicating that apes are susceptible to SFV superinfection, including highly divergent strains from other primate species.